Identification of Microplastics in Water Column at Koto Panjang Dam, Kampar Regency, Riau Province - Muhammad Edy; Budijono Budijono; Muhammad Hasbi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
In PLTA Koto Panjang Dam, plastic waste comes from various community activities and fishery activities. The waste is destroyed into small particles (0.3-5mm) called microplastics. To determine the presence of microplastics in the water column, a study was conducted in December 2020 - February 2021. Water samples were taken from 3 stations with 3 sampling points at 3 different depths using Water Sampler. 250 ml of water was taken and filtered using a plankton net plankton no. 25. To obtain the microplastics, the filtered water was again filtered using Whatman filter paper No.42 and the type of microplastics were identified using a binocular microscope. The results of the study were found to be fiber, film and fragments. The abundance of microplastics ranged from 22 to 533.33 particles/m3. The highest total abundance is at station 3 with fiber type at a depth of 3 meters at 533.33 particles/m3. While the lowest abundance type is at station 1 with a film type at a depth of 6 m as many as 22 particles/m3.